Evidence for the involvement of FXR signaling in ovarian granulosa cell function - Kentaro TAKAE; Mizuho NAKATA; Takafumi WATANABE; Hiroshi SASADA; Hiroshi FUJII; Ikuo TOMIOKA (The Society for Reproduction and Development, 2018)
Farnesoid X receptor (FXR) is mainly present in enterohepatic tissues and regulates cholesterol, lipid, and glucose homeostasis in coordination with target genes such as SHP and FABP6. Although FXR has been revealed to be expressed in reproductive tissues, FXR function and expression levels in the ovary remain unknown. In this study, we investigated FXR expression in mouse ovaries and its target genes in ovarian granulosa cells. In situ hybridization and immunohistochemical staining showed that FXR was mainly distributed in secondary and tertiary follicles. The agonist-induced activation of FXR in cultured granulosa cells induced the expression of SHP and FABP6, while siRNA targeting of FXR decreased CYP19a1 and HSD17b1 expression. Upon examination of the roles of SHP and FABP6 in granulosa cells, we found that SHP overexpression significantly decreased StAR, CYP11a1, and HSD3b gene expression. In addition, siRNA targeting of FABP6 decreased CYP19a1 and HSD17b1 expression, while FABP6 overexpression increased CYP19a1 expression. In conclusion, the present study demonstrates the presence of FXR signaling in the ovary and reveals that FXR signaling may have a role in function of granulosa cells.